Peptic Ulcer Healing Activity of Fruit Pulp Extract and Seed Oil of Adansonia digitata Linn (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
Adansonia digitata (AD) Linn has been used to cure PU in Ayurveda but its efficacy has not been validated. The current study was so carried out to evaluate the antiulcer activity of ethanolic extract of Adansonia digitata fruit pulp (ADFP), n hexane extract of Adansonia digitata seed oil (ADSO) & their combination (ADFP+ADSO) in rats. The effect of AD on gastric ulcer in pylorus ligation induced and ethanol induced models was studied using doses [ADFO (500 mg/kg), ADSO (300 mg/kg) & combination of ADFP & ADSO] for 10 days. Omeprazole (10 mg/kg) were used as the standard drug. Depending on the model, outcomes measures were gastric volume, pH, free acidity, total acidity, ulcer index, percentage inhibition of ulcer index, protein, pepsin, mucus, antioxidant marker enzyme level (Superoxide dismutase, Catalase, Lipid peroxidation), morphological & Histopathological study. The result obtained with combination was set up near to the standard drug and consequence showed that the combination of ADFP & ADSO was found to be more effective than the individual extract of AD. The outcomes were statistically evaluated with the one-way ANOVA followed by the test of Dennett’s‘t’. The secondary-metabolites such as flavonoids, proteins, saponins, tannins, phenols, terpenoids, alkaloids and Fatty acids (palmitic acid, oleic acid, linoleic acid) are potent as antioxidant, antiulcer and anti-inflammatory. The finding of this reading confirmed that AD has antiulcer activity due to 1 or more of the secondary-metabolites present in it. Therefore, this study validates its antiulcer use in Ayurveda. Future investigation on separation of specific phytochemicals and elucidate MOA are needed.